Exhaled carbon monoxide in children with asthma and allergic rhinitis - Yulia Fatma Wardani; Rina Triasih; Amalia Setyati (Paediatrica Indonesiana, 2022)
Background Exhaled carbon monoxide has been related to the degree of inflammation. An easy, inexpensive, and non-invasive test to measure exhaled CO levels (eCO) may help in supporting the diagnosis of asthma and allergic rhinitis (AR) in children. Objective To compare the eCO levels in children with asthma, AR, or both asthma and AR, to children without asthma or AR. Methods This was a cross-sectional study involving 450 children aged 13-14 years in Yogyakarta. Asthma and AR were determined according to the International Study of Asthma and Allergies in Childhood (ISAAC) study criteria, while eCO level was examined using a SmokerlyzerÂ®. The levels of eCO between groups were analyzed using Kruskal-Wallis and Mann-Whitney tests. Results Of 450 children, 48 (10.67%) had asthma only, 91 (20.22%) had AR only, 67 (14.89%) had both asthma and AR, and 244 (54.22%) had neither asthma nor AR. The eCO levels of children with asthma or AR were not significantly different compared to those without asthma and AR (P=0.33 and P=0.19, respectively). However, children with both asthma and AR had significantly higher eCO level compared to children without asthma and AR (P< 0.001). Conclusion The levels of eCO in children with asthma only or AR only are similar to those without both diseases. Children with both asthma and AR have significant higher eCO compared to healthy children.